2000
DOI: 10.1152/ajplung.2000.279.2.l216
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein A enhances mycobacterial killing by rat macrophages through a nitric oxide-dependent pathway

Abstract: Surfactant-associated protein A (SP-A) is involved in surfactant homeostasis and host defense in the lung. We have previously demonstrated that SP-A specifically binds to and enhances the ingestion of bacillus Calmette-Guerin (BCG) organisms by macrophages. In the current study, we investigated the effect of SP-A on the generation of inflammatory mediators induced by BCG and the subsequent fate of ingested BCG organisms. Rat macrophages were incubated with BCG in the presence and absence of SP-A. Noningested B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 43 publications
5
65
1
Order By: Relevance
“…In vitro studies conducted on the direct effects of lung collectins on alveolar macrophages have been somewhat controversial because they found both stimulation [27][28][29][30] and inhibition 27,[31][32][33] of proinflammatory functions, including TNF-α production. 34 Only a few studies described the effects of SP-A and SP-D on dendritic cell function.…”
Section: Tnf; Sp-d; Dendritic Cell; Mouse Model; Airway Inflammationmentioning
confidence: 99%
“…In vitro studies conducted on the direct effects of lung collectins on alveolar macrophages have been somewhat controversial because they found both stimulation [27][28][29][30] and inhibition 27,[31][32][33] of proinflammatory functions, including TNF-α production. 34 Only a few studies described the effects of SP-A and SP-D on dendritic cell function.…”
Section: Tnf; Sp-d; Dendritic Cell; Mouse Model; Airway Inflammationmentioning
confidence: 99%
“…Earlier studies showed that SP-R210 mediates phagocytosis and killing of SP-A-opsonized Mycobacterium bovis BCG (SP-A-BCG) by bone marrowderived macrophages (23). These studies showed that ligation of SP-R210 with SP-A-BCG complexes enhanced expression of TNF␣ and nitric oxide that enabled macrophages to control mycobacterial growth (23,26). On the other hand, SP-R210 can control the level of inflammatory cells and mediators in the presence of mycobacterial extracts, suggesting a secondary role of SP-R210 in immune homeostasis (27).…”
mentioning
confidence: 99%
“…The late induction of these cytokines indicates that their increase may not be the primary response to FGF-3 induction but a response to an alteration in pulmonary gene expression. SP-A has been found to promote macrophage phagocytosis (32) and chemotaxis (33). Induction of SP-A by FGF-3 may play a role in the FAM phenotype.…”
Section: The Effects Of Fgf-3 Induction On the Expression Of Cytokinementioning
confidence: 99%
“…First, the chronic high level of the expression of FGF-3 could alter the differentiation of Clara cells, which could be manifested in a reduction in the expression of these cell-specific markers. Second, inflammatory cytokines may have affected expression of these genes directly and͞or the phenotype of airway epithelial cells (32,33). Finally, and more likely, the increase in the number of alveolar type II cells could result in the dilution of Clara cell-specific mRNA, because the proportion of airway cells in the lung could decrease with the increase in distal cells.…”
Section: The Effects Of Fgf-3 Induction On the Expression Of Cytokinementioning
confidence: 99%
See 1 more Smart Citation